2021
DOI: 10.1108/idd-12-2020-0155
|View full text |Cite
|
Sign up to set email alerts
|

The effect of consumer self-confidence on information search and share intention

Abstract: Purpose The knowledge about a specific product develops self-confidence among consumers and facilitates them to share and search for information. This study aims to highlight the effects of consumer’s self-esteem on search and share intentions of information. Furthermore, this relationship was analyzed through the mediation of subjective knowledge (SK). Design/methodology/approach The data were collected from 1,136 Chinese respondents having a perception of purchasing cellphones. To analyze the data, check i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…Siyambalapitiya et al (2018) suggested that if green practices in the workplace increase employee characteristics such as motivation, and competence, financial performance may improve as a result. Employers who take environmental responsibility into account when recruiting workers, or at least show they care about the environment, will draw candidates who will be drawn to the company's environmental consciousness (Tariq et al, 2016;Jamil et al, 2021a). Developing and encouraging the environment's interests and activities can also be helpful for companies, as it can result in increased skill and motivation, better retention and productivity, and overall improved Ec.P.…”
Section: Green Human Resource Management Bundles and Sustainable Perf...mentioning
confidence: 99%
“…Siyambalapitiya et al (2018) suggested that if green practices in the workplace increase employee characteristics such as motivation, and competence, financial performance may improve as a result. Employers who take environmental responsibility into account when recruiting workers, or at least show they care about the environment, will draw candidates who will be drawn to the company's environmental consciousness (Tariq et al, 2016;Jamil et al, 2021a). Developing and encouraging the environment's interests and activities can also be helpful for companies, as it can result in increased skill and motivation, better retention and productivity, and overall improved Ec.P.…”
Section: Green Human Resource Management Bundles and Sustainable Perf...mentioning
confidence: 99%
“…The desire to get rewards through promotional deals, free coupons, and other loyalty incentives contribute to remuneration motivation. Promotional incentives are considered essential predictors of consumer responses to any marketing offer and contribute to positive purchasing intentions ( Femenia-Serra and Gretzel, 2020 ; Jamil et al, 2021b ). The consumer commitment to retailers/brands has been very beneficial in the ordinary sense of providing customer benefits in online settings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Companies with more substantial strategic capabilities in social media have better access to information and technology critical to success. Such firms will benefit from such capabilities by gaining access to unique data, technology, and support and responding to environmental changes more proactively ( Saavedra et al, 2014 ; Jamil et al, 2021a ). It can take a while for start-ups without affiliations and limited resources to build such a capability.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%